Fragment-based drug discovery and mechanistic studies of human thymidylate synthase - Chen, Dan (Nanyang Technological University, 2016)
Human thymidylate synthase (hTS) is the sole enzyme responsible for de novo biosynthesis of dTMP and is vital to cell proliferation and survival. Inhibition of hTS has been explored and found to be effective in cancer chemotherapy, while the efficacy is limited by drug resistance. Herein fragment screening is applied to hTS to identify novel start point for drug design. Four types of hits are found, of which two are progressed to structure- and biophysics-driven drug design due to novel binding modes in the active site. The elaborated compounds show significant improvements in affinities and open new avenues for development of hTS inhibitors to overcome drug resistance. Meanwhile, another type of hit reveals a potential allosteric site of hTS possibly involved in regulating overexpression-induced drug resistance to hTS inhibitors.